Three-dimensional chitin-based scaffolds from Verongida sponges (Demospongiae: Porifera): part II, biomimetic potential and applications - Ehrlich, Hermann; Steck, Eric; Ilan, M.; Maldonado, M.; Muricy, G.; Bavestrello, G.; Kljajic, Z.; Carballo, J. L.; Schiaparelli, S.; Ereskovsky, A.; Schupp, P.; Born, R.; et al. (International journal of biological macromolecules, 2010)
In order to evaluate the biomedical potential of three-dimensional chitinous scaffolds of poriferan origin, chondrocyte culturing experiments were performed. It was shown for the first time that freshly isolated chondrocytes attached well to the chitin scaffold and synthesized an extracellular matrix similar to that found in other cartilage tissue engineering constructs. Chitin scaffolds also supported deposition of a proteoglycan-rich extracellular matrix of chondrocytes seeded bioconstructs in an in vivo environment. We suggest that chitin sponge scaffolds, apart from the demonstrated biomedical applications, are highly optimized structures for use as filtering systems, templates for biomineralization as well as metallization in order to produce catalysts.
Gesehen am 02.03.2023